The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13578-018-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0027599/PHDLA1 suppresses gastric cancer progression by sponging miR-101-3p.1

Abstract: BackgroundPleckstrin homology-like domain family A member 1 (PHLDA1) is a tumor suppressor gene in gastric cancer, but its role regulated by circular RNAs (circRNAs) is not known. CircRNAs are important regulators in cancer growth and progression, however, the molecular roles of circRNAs in gastric cancer are rarely known. The study was aimed to investigate the role of circRNAs in regulating PHLDA1 expression in gastric cancer.ResultsThe circRNA expression profile in the gastric cancer tissues by circRNA micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Emerging evidence has shown that circRNAs could regulate cancer cell proliferation by inhibiting the downstream microRNAs targets, and this is called "cavernous mechanism". For example, Wang et al indicated that circ_0027599 suppresses the gastric cancer progression by sponging miR-101-3p [24]. Chen et al reported that circ_100395 regulated miR-1228/TCF21 pathway to inhibit lung cancer progression [17].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown that circRNAs could regulate cancer cell proliferation by inhibiting the downstream microRNAs targets, and this is called "cavernous mechanism". For example, Wang et al indicated that circ_0027599 suppresses the gastric cancer progression by sponging miR-101-3p [24]. Chen et al reported that circ_100395 regulated miR-1228/TCF21 pathway to inhibit lung cancer progression [17].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al disclosed that enforced circ_0027599 expression suppressed cell proliferation and metastasis in GC. 11 Other like circ_101882 was unveiled to promote cell migration and invasion in GC. 12 Nevertheless, the effects and mechanism of circ_ASAP2 in GA-mediated GC process are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Rescue experiments showed that miR-1200-inhibitor abrogated the decrease of cell proliferation and the increase of cell apoptosis in CDDP-resistant gastric cancer cells induced by circ_0026359 knockdown on exposure to CDDP; miR-1200-inhibitor also abolished the decrease of IC50 for CDDP induced by circ_0026359 depletion in SGC-7901/CDDP cells. As reported previously, many circRNAs (including circ_ 0066444, circ_0027599, and circ_0000673) played important roles in proliferation and metastasis of human gastric cancer cells [26][27][28]. circ_0081143 was demonstrated to promote cisplatin resistance in gastric cancer cells through targeting miR-646/CDK6 pathway [20].…”
Section: Discussionmentioning
confidence: 61%